PENGARUH PERILAKU PEMIMPIN DAN KOMITMEN KARYAWAN TERHADAP PRESTASI KERJA KARYAWAN PADA PT. META TANI PALMA ABADI - Sulitra, Beni Okta; Arini, Eti (UM. Bengkulu, 2025)
Considering the importance of employee work performance, employee commitment is one of the factors that needs to be paid attention to by company leaders. Problem formulation 1) Does leader behavior influence employee work performance at PT. Meta Tani Palma Abadi? 2) Does employee commitment influence employee work performance at PT. Meta Tani Palma Abadi? 3) Does leader behavior and employee commitment simultaneously influence employee work performance at PT. Meta Tani Palma Abadi? This research aims 1) To find out how leader behavior influences employee work performance at PT. Meta Tani Palma Abadi. 2) To find out how employee commitment influences employee work performance at PT. Meta Tani Palma Abadi. 3) To find out how leader behavior and employee commitment simultaneously influence employee work performance at PT. Meta Tani Palma Abadi. This type of research is a quantitative approach. The method used in this research is a descriptive method. The population of this research is the entire number of employees of PT. Meta Tani Palma Abadi, totaling 134 people. The sample consisted of 134 employees of PT. Meta Tani Palma Abadi. Based on the results of research regarding leader behavior (X1) which influences employee performance (Y) at PT Meta Tani Palma Abadi, this means that if work commitment increases, employee performance will also increase. Commitment (X2) influences employee performance (Y) PT Meta Tani Palma Abadi meaning that if the personality is good then employee performance is also good Employee performance (Y) on employee performance PT Meta Tani Palma Abadi means that if employee commitment increases then employee performance also increases . Keywords: Leader behavior, employee commitment, work performance,